Obtaining and optical properties of the glasses of the GeS₂–HgS system - Nechyporuk, B.D.; Olekseyuk, I.D.; Yukhymchuk, V.O.; Filonenko, V.V.; Mazurets, I.I.; Parasyuk, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The glassy alloys of the GeS₂–HgS system in the range of 0–50 mol. % HgS
were obtained by the melt quenching technique. Their Raman spectra were investigated.
The dependence of the particularities of the light scattering bands on the chemical
composition was analyzed.